Persistence and clearance of high‐risk human papillomavirus and cervical dysplasia at 1 year in women living with human immunodeficiency virus: a prospective cohort study. (14th June 2021) - Luckett, R; Painter, H; Hacker, MR; Simon, B; Seiphetlheng, A; Erlinger, A; Eakin, C; Moyo, S; Kyokunda, LT; Esselen, K; Feldman, S; Morroni, C; et al.
Abstract : Objective: Evaluate 1‐year outcomes of cervical cancer screening and treatment using primary high‐risk human papillomavirus (HPV) testing in women living with human immunodeficiency virus (HIV). Design: Prospective cohort study. Setting: HIV treatment centre in Botswana. Population: Women living with HIV. Methods: Participants underwent cervical cancer screening with high‐risk HPV testing and triage evaluation at baseline and 1‐year follow up. Excisional treatment was offered as indicated. Histopathology was the reference standard. Main outcome measures: Persistence, clearance and incidence of high‐risk HPV infection; and persistence, progression, regression, cure and incidence of cervical dysplasia. Results: Among 300 women screened at baseline, 237 attended follow up (79%). High‐risk HPV positivity significantly decreased from 28% at baseline to 20% at 1 year ( P = 0.02). High‐risk HPV persistence was 46% and clearance was 54%; incidence was high at 9%. Prevalence of cervical intraepithelial neoplasia Grade 2 (CIN2) or higher was most common in participants with incident high‐risk HPV (53%). CIN2 or higher was also common in those with persistent high‐risk HPV (32%) and even in those who cleared high‐risk HPV (30%). Of the high‐risk HPV‐positive participants at baseline with <CIN2, 40% progressed to CIN2 or higher at follow up. Conclusion: The high incidence of high‐risk HPV and high‐grade cervical dysplasia in women living with HIV after one round of high‐risk HPV‐based screening and treatment raises concern about the rate of progression of high‐risk HPV infection to dysplasia. Persistent disease is common. Caution in spacing cervical cancer screening intervals using high‐risk HPV testing in women living with HIV is warranted. Tweetable abstract: High incidence and persistence of HPV and CIN2+ in women living with HIV 1 year after screening and treatment. Tweetable abstract: High incidence and persistence of HPV and CIN2+ in women living with HIV 1 year after screening and treatment.